"Involve me and I learn": Teaching and applying anthropology. Issue 2 (November 2016) - COPELAND, TONI J.; FRANÇOIS DENGAH, H. J.
Abstract : The role of anthropology to inform and shape public discourse has never been more necessary. Yet, the discipline struggles, at times, to remain relevant and accessible to students. It is increasingly important to provide students with skills that are useful outside academia. The ability to make the anthropological research process accessible is a critical determinate of the future of our discipline. This introduction situates the articles of this issue in a discussion of mentorship and hands‐on training for students. Drawing on discussions within anthropology, social sciences, and education, it addresses the importance of training undergraduate and graduate students in methods that connect professional and community needs. Examples of engaging students and communities with "hands‐on" anthropological experiences are highlighted within diverse themes including health, community, gender, volunteer tourism, online virtual worlds, and technology, serving as frameworks for extending and connecting research with students, faculty, and community members.